FRiskA - Food Safety and Nutritional Risk Assessment: assessing existing and emerging risks in the food chain (and benefits): twinning project - Fernandes, Paulo (2019)
FRiskA (Food safety and nutritional Risk Assessment) Twinning project. Twinning aims at significantly strengthening a defined field of research in a university or research organisation from a Widening country by linking it with at least two internationally-leading research institutions in other Member States or Associated Countries. Consortium - The 2 chosen mentor institutions were: Danmarks Tekniske Universitet - Denmark; Istituto Superiore di Sanita – Italy. Objectives INSA: Upgrade INSA’s R&D capacity by expanding the staff potential and fostering a critical mass of researchers with inter-disciplinary expertise in the area of microbiological and chemical food risk assessment; Increase INSA’s networking activities on food safety with other official organizations, academia, associations and food business operators; Increase the publication of peer-reviewed scientific articles relevant to risk assessment; Increase the average impact factor of the publications relevant to risk assessment; Increase the success rate of international project applications related to food safety and nutrition.